MUHAMMAD PBUH AND HIS CONTRIBUTIONS TO THE DEVELOPMENT OF RULE OF LAW AND SOCIAL JUSTICE IN THE 7th CENTURY - Omotosho, A.O. (Jurnal Syariah, 2011)
Islam and Christianity are the closest religions when compared with other religions, next to Judaism. Yet they are very antagonist to each other. A close look to creeds of the two religions reveal that the two have so much in common, sufficient enough to prevent the level of rivalry that has characterized their relationship for centuries. In spite of advancement in knowledge and modern facilities that suppose to have bridged the gap, the hostility continues. This article attempts to observe the reasons for this endless rivalry which are caused by many factors which include political, cultural, economical, and lack of awareness for each other’s teachings, as a modest contribution to bridging the problem of lack of awareness of each other’s teachings by tracing the history of Prophet Muhammad PBUH, the founder of Islam and his efforts to reform his society most especially the rule of law.